Implementação de células móveis de produção alinhadas com a técnica de linha de balanço para melhorias dos processos produtivos - UGULINO, Janilton Maciel (Universidade Federal do Pará, 2013)
In this work we presented the result of an exploratory study investigating the insert in a horizontal work the application of the concept of "production mobile cell" for the Civil Construction. This research was conducted in an evolutionary process between a work of vertical and horizontal features; The study was addressed for production mobile cells, that is to say, cells that retains all the characteristics of the cell of traditional manufacture, even so with the characteristic of the mobility through the product, the work compares like this and it illustrates the results obtained with this form of the workers' organization before the productivity data and cost originating from of works executed previously.